2013
DOI: 10.3748/wjg.v19.i4.561
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on efficacy of reduced cathartic bowel preparation with polyethylene glycol and bisacodyl

Abstract: Administration of 10 mg bisacodyl enteric-coated tablets prior to or after oral administration of 2 L PEG-4000 electrolyte solution enhances stool and fluid cleansing ability, and has no impact on the attenuation value of residual fluid or the discomfort index. The former is an excellent alternative for CTC colorectum cleansing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In a previous experience, we found similar results by administering three sachets/day of a Macrogol 3350-based mild laxative starting 2 days before CTC (4.4% of insufficiently marked segments) [ 13 ]. Iafrate et al [ 8 ] reported 2.6% of colon segments with insufficient preparation using a 1L PEG solution associated with a stimulant agent (bisacodyl) that is correlated with a higher stool cleansing ability [ 14 ]. Both in our experience and in that of the two above-mentioned studies, FT quality decreased in the distal colonic segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous experience, we found similar results by administering three sachets/day of a Macrogol 3350-based mild laxative starting 2 days before CTC (4.4% of insufficiently marked segments) [ 13 ]. Iafrate et al [ 8 ] reported 2.6% of colon segments with insufficient preparation using a 1L PEG solution associated with a stimulant agent (bisacodyl) that is correlated with a higher stool cleansing ability [ 14 ]. Both in our experience and in that of the two above-mentioned studies, FT quality decreased in the distal colonic segments.…”
Section: Discussionmentioning
confidence: 99%
“…Polyethylene glycol (PEG) is a hydrophilic and iso-osmolar laxative that has few side effects since it is non-absorbable and does not alter the patient's electrolyte balance. PEG has been proposed in low-volume solutions either in a single or fractionated dose [10][11][12][13][14][15][16][17]. A variable amount of residual fluid is usually present in the large bowel following PEG administration that can easily be tagged by oral intake of iodinated contrast media, which has been extensively evaluated [13,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…CTC has been shown to be a new effective tool for colorectal cancer screening, due to its non-invasiveness and high sensitivity for polyp and neoplasia detection [ 12 16 ]. However, its hazard of ionizing radiation is a major concern to the public [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The iso-osmotic bowel cleansing agent polyethylene glycol-4000 (PEG-4000) causes diarrhea by increasing the local osmotic pressure, which generates mechanical movement of water ions to clean the intestinal tract, achieving a good bowel cleansing effect. Furthermore, PEG-4000 is widely used in clinical practice because of its good reliability and safety (Di Nardo et al 2014 ; Chen et al 2013 ; Abe et al 2021 ). However, PEG-4000 has a poor taste and requires a large intake of liquid, which may cause discomfort to patients, including nausea, vomiting, bloating, and electrolyte and intestinal microbiota disorders (Nyberg et al 2010 ; Yoshioka et al 2017 ; Chaussade and Minić 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…221,104) was purchased from Staidson Biopharmaceuticals Co., Ltd., Beijing, China. The syrup was purchased from Yingzhihao Biotechnology Co., Liaoning, China (Chen 2011, Chen 2012Chen et al 2013). The food production license number and product standard code of the syrup in China are SC10637148204742 and GB7101, respectively.…”
Section: Introductionmentioning
confidence: 99%